2019
DOI: 10.4132/jptm.2018.11.13
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Cortical Neoplasm with Uncertain Malignant Potential Arising in the Heterotopic Adrenal Cortex in the Liver of a Patient with Beckwith-Wiedemann Syndrome

Abstract: Patients with Beckwith-Wiedemann syndrome (BWS) are predisposed to developing embryonal tumors, with hepatoblastoma being the most common type. Our patient showed hemihypertrophy, macroglossia, and paternal uniparental disomy in chromosome 11 and was diagnosed with BWS. When the patient was 9 months old, a 2.5×1.5 cm oval hypoechoic exophytic mass was detected in the inferior tip of his right liver. Preoperative imaging identified it as hepatoblastoma; however, histologic, immunohistochemistry, and electron mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In our series, inhibin-a was negative in three cases and had weak focal expression (occasional cells) in two cases. Focal immunoreactivity for inhibin-a was also seen in heterotopic ACT in a patient with BWS (29). However, the clinical and pathological significance of immunoreactivity for inhibin a remains unclear.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In our series, inhibin-a was negative in three cases and had weak focal expression (occasional cells) in two cases. Focal immunoreactivity for inhibin-a was also seen in heterotopic ACT in a patient with BWS (29). However, the clinical and pathological significance of immunoreactivity for inhibin a remains unclear.…”
Section: Discussionmentioning
confidence: 96%
“…A diversity of adrenal gland lesions is observed in BWS, including adrenal hyperplasia, hemorrhage, cysts, neuroendocrine tumors, neuroblastoma, hemangioendothelioma, ovarian thecal metaplasia, and adrenal cortical tumors (adenoma and carcinoma) (28). Moreover, ectopic adrenal tissue (29) has been found in liver, renal hilum, and spinal cord. A panel of markers (CD56, vimentin, melan-A, inhibin-a, synaptophysin, chromogranin and SF-1) are used to establish the origin of adrenal tumors (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In large worldwide cohorts (total: 2,256), where tumor type has been correlated with molecular subtypes, the following tumor types have been identified in UPD(11)pat (79/346): 31 Wilms tumors, 22 hepatoblastomas, 8 adrenocortical carcinomas, 5 neuroblastomas, 3 pheochromocytomas, 3 nephroblastomas, 2 leukemias, 1 ganglioneuroma, 1 hemangiotelioma, 1 myopepithelial cell carcinoma, 1 pancreatoblastoma, and 1 rhabdomyosarcoma (Alsultan et al, 2008 ; Bliek et al, 2004 ; Brioude et al, 2013 ; Cöktü et al, 2020 ; Eltan et al, 2020 ; Gaston et al, 2001 ; Hertel et al, 2003 ; H’mida Ben‐Brahim et al, 2015 ; Ibrahim et al, 2014 ; Kim et al, 2019 ; Maas et al, 2016 ; Mussa, Molinatto, et al, 2016 ; Mussa, Russo, et al, 2016 ; Sasaki et al, 2007 ; Weksberg et al, 2001 ; Wijnen et al, 2012 ; Table 3 ). This underlines the great variability of tumor types in this molecular subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenocortical tumors were also reported in five studies by IC2‐LOM with pauci‐symptomatic presentation and described in UPD(11)pat in large studies where the phenotype was not well reported (Alsultan et al, 2008 ; Bliek et al, 2004 ; Brioude et al, 2013 ; Cöktü et al, 2020 ; Eltan et al, 2020 ; Gaston et al, 2001 ; Hertel et al, 2003 ; H’mida Ben‐Brahim et al, 2015 ; Ibrahim et al, 2014 ; Kim et al, 2019 ; Maas et al, 2016 ; Mussa, Molinatto, et al, 2016 ; Mussa, Russo, et al, 2016 ; Sasaki et al, 2007 ; Weksberg et al, 2001 ; Wijnen et al, 2012 ; Table 3 ). Kim et al described a patient with hemihypertrophy and macroglossia related to UPD(11)pat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation